2019
DOI: 10.3389/fncel.2019.00299
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Human Mast Cells With Respect to MRGPRX2 Receptor Expression and Function

Abstract: Mast cells and their mediators play a role in the control of homeostasis and in the pathogenesis of several disorders. The concept of rodent mast cell heterogeneity, initially established in the mid-1960s has been extended in humans. Human mast cells isolated and purified from different anatomic sites can be activated via aggregation of cell surface high affinity IgE receptors (FcεRI) by antigens, superantigens, anti-IgE, and anti-FcεRI. MAS-related G protein-coupled receptor-X2 (MRGPRX2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 102 publications
1
70
0
Order By: Relevance
“…IL-33 was found to synergize with SP in promoting TNF-α expression; IL-33 was shown to upregulate surface NK-1 expression [45]. MRGPRX2 has been detected in skin MCs and synovial MCs but not lung MCs, suggesting CTMCs may be more susceptible to this signaling and thus be the source of pathogenic inflammation in disease states [92].…”
Section: Conclusion/summarymentioning
confidence: 99%
“…IL-33 was found to synergize with SP in promoting TNF-α expression; IL-33 was shown to upregulate surface NK-1 expression [45]. MRGPRX2 has been detected in skin MCs and synovial MCs but not lung MCs, suggesting CTMCs may be more susceptible to this signaling and thus be the source of pathogenic inflammation in disease states [92].…”
Section: Conclusion/summarymentioning
confidence: 99%
“…168 Opioids and opiates have long been known to degranulate MCs 37,89 and recent overexpression and knockdown strategies hinted at MRGPRX2 as the preferential receptor 25,169 (Table II). A recent study demonstrated that human skin MCs degranulate in response to morphine and SP whereas lung or heart MCs do not, 13 corroborating the preferential expression of MRGPRX2 on skin MCs. 12 Whether endogenous opioids contribute to chronic inflammatory skin diseases, such as AD or urticaria, is currently unknown.…”
Section: Activation Of Mrgprx2 By Proteasesmentioning
confidence: 72%
“…7 In line with this, skin MC TC s but not lung MC T s degranulated in response to basic compounds, such as compound 48/80 (C48/80) and substance P (SP) via MRGPRX2. 7,11,12 Furthermore, PCR and microarray data showed that MRGPRX2 is expressed at high levels in human skin and synovial MC TC s but at low levels in lung MC T s. 13 Notably, expression of MRGPRX2 decreased in primary human skin MCs with time of cultivation, decreasing approximately 10-fold within 4 to 5 weeks in culture. 8 In addition, maintenance of human skin MCs in culture with stem cell factor (SCF) and IL-4 downregulated the expression of MRGPRX2 as well as MRGPRX2-triggered degranulation.…”
Section: Expression Of Mrgprx2 On Mcsmentioning
confidence: 99%
“…For instance, lung mast cells express high levels of TLRs, while skin mast cells exhibit low levels of this class of receptors [54]. Moreover, anti-IgE-mediated activation was recently shown to cause higher release of LTC 4 and PGD 2 from isolated lung mast cells, compared to their skin, heart and synovial cavity counterparts [55]. On the other hand, substance P, a MRGPRX2 agonist, failed to induce lipid mediator production from lung mast cells and caused no histamine and tryptase release from both lung and heart mast cells, whereas it induced a significant concentration-dependent release of these mediators from skin mast cells [55].…”
Section: Mast Cellsmentioning
confidence: 99%
“…Moreover, anti-IgE-mediated activation was recently shown to cause higher release of LTC 4 and PGD 2 from isolated lung mast cells, compared to their skin, heart and synovial cavity counterparts [55]. On the other hand, substance P, a MRGPRX2 agonist, failed to induce lipid mediator production from lung mast cells and caused no histamine and tryptase release from both lung and heart mast cells, whereas it induced a significant concentration-dependent release of these mediators from skin mast cells [55]. In the lungs, the main population of mast cells is of the MC T type, which is located mainly in the bronchial and bronchiolar lamina propria [54,56].…”
Section: Mast Cellsmentioning
confidence: 99%